Imaging of the equatorial ionosphere - C. N. Mitchell (Annals of Geophysics, 2005)
The equatorial anomaly is the dominant structure in free electron concentration in the tropical ionosphere. Due
to its edges (crests) which are characterised by steep latitudinal gradients in TEC and are temporally and spatially
variable, it is one of the ionospheric regions most difficult to image with inversion methods. In this paper
we reconstruct an International Reference Ionosphere model of the equatorial ionosphere by employing a grid
of virtual ground GPS receivers and actual GPS satellite positions. The MIDAS algorithm, an inversion method
for reconstructing the ionosphere as a linear composition of given empirical orthogonal functions, is used. Comparing
the true model ionosphere with the resulting images a fine tuning of the basis functions (vertical profile
contraints) in the inversion is realised.